Effects of Rice Varieties on Attractiveness, Population Development, and Weight Loss Caused by Sitophilus oryzae During Storage - Dicky Marsadi; Ketut Ayu Yuliadhi (Journal of Biodiversity and Biotechnology, 2025)
Sitophilus oryzae is one of the major pests of stored rice, causing both quantitative and qualitative losses during storage. This study aimed to analyze the effects of different rice varieties on attractiveness, population development, and weight loss resulting from S. oryzae infestation. The research was conducted using a free-choice attractiveness test, population development observations, and weight loss measurements on four rice varieties, namely red rice, white rice, black rice, and brown rice. The results indicated that rice variety significantly affected the behavior and population development of S. oryzae. Red rice exhibited the highest level of attractiveness and the greatest population growth rate, followed by black rice and brown rice, whereas white rice showed the lowest attractiveness, population growth rate, and weight loss. The pattern of rice weight loss corresponded to pest population levels, with varieties harboring higher S. oryzae populations experiencing greater percentages of weight loss. Differences in S. oryzae responses among rice varieties are likely associated with variations in the physical and chemical characteristics of the grains, particularly nutrient content and grain layer structure, which influence feeding preference and developmental success of the pest. These findings suggest that rice varieties have potential as an important component of postharvest pest management strategies, especially in reducing storage losses through the selection of varieties that are relatively more resistant to S. oryzae infestation.